STRATEGI PEMASARAN DIGITAL BERBASIS MEDIA SOSIAL DALAM MEMPERKUAT KEUNGGULAN KOMPETITIF UMKM SMOOTHIES KING MANGO THAI - Fitrianingsih Fitrianingsih; Suwadi Suwadi (Smart Education, 2025)
Abstract: The rapid development of digital technology has transformed the marketing practices of Micro, Small, and Medium Enterprises (MSMEs), encouraging business owners to utilize social media as a platform for promotion, communication, and customer relationship development. This study aims to analyze the implementation of a social media-based digital marketing strategy in strengthening the competitive advantage of Smoothies King Mango Thai MSME in Tebing Tinggi City. The research employed a descriptive qualitative approach involving seven informants, consisting of one business owner and six customers. Data were collected through interviews, observations, and documentation, and were analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that social media is utilized as a medium to introduce products, disseminate promotional information, establish communication with customers, and expand the reach of marketing information. From the business owner's perspective, digital media has become an integral part of marketing activities, while customers perceive social media as an effective source of information regarding products and promotional offers. The study also reveals that competitive advantage is not solely shaped by digital marketing activities but is also influenced by product quality, pricing, service quality, business location, and customer experience. Furthermore, the findings suggest that digital marketing strategies are more effective when integrated with customer engagement initiatives and supported by the delivery of superior value to consumers. Keywords: Digital Marketing, Social Media, Customer Engagement, MSMEs, Competitive Advantage Abstrak: Perkembangan teknologi digital telah mengubah pola pemasaran UMKM dan mendorong pelaku usaha untuk memanfaatkan media sosial sebagai sarana promosi, komunikasi, dan pengembangan hubungan dengan pelanggan. Penelitian ini bertujuan menganalisis penerapan strategi pemasaran digital berbasis media sosial dalam memperkuat keunggulan kompetitif UMKM Smoothies King Mango Thai di Kota Tebing Tinggi. Penelitian menggunakan pendekatan kualitatif deskriptif dengan tujuh informan yang terdiri atas satu orang pengelola usaha dan enam orang pelanggan. Data dikumpulkan melalui wawancara, observasi, dan dokumentasi, kemudian dianalisis melalui proses reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa media sosial digunakan sebagai sarana untuk memperkenalkan produk, menyampaikan informasi promosi, membangun komunikasi, dan memperluas jangkauan informasi kepada konsumen. Perspektif pengelola usaha menunjukkan bahwa media digital menjadi bagian dari aktivitas pemasaran, sedangkan perspektif pelanggan menunjukkan bahwa media sosial membantu memperoleh informasi mengenai produk dan promosi. Keunggulan kompetitif tidak hanya dibentuk oleh aktivitas pemasaran digital, tetapi juga oleh kualitas produk, harga, pelayanan, lokasi, dan pengalaman pelanggan. Temuan penelitian menunjukkan bahwa strategi pemasaran digital akan lebih efektif apabila dikombinasikan dengan customer engagement dan kualitas nilai yang ditawarkan kepada konsumen. Kata kunci: Pemasaran Digital, Media Sosial, Customer Engagement, UMKM, Keunggulan Kompetitif.